Effectiveness of Virtual Reality-Based Health Promotion and Safety Training in Schools - Fifit Eka Furi Astutik; Reno Bagas Andrean (Poltekkes Kemenkes Surabaya, 2026)
Health and safety within the school environment are essential to ensuring a secure and sustainable learning process. Data from the Ministry of Health (2022) indicate that only 45% of secondary schools have an established emergency preparedness programme. A preliminary assessment at SMK Atisa Dipamkara also revealed substantial gaps: 73% of students had never participated in a fire simulation, and existing training remained conventional without interactive media. Nutritional issues were similarly prominent, as 60% of students frequently skipped breakfast, potentially impairing concentration and physical endurance. This study examined the effectiveness of a virtual reality (VR)-based training model integrating fire emergency simulation and balanced nutrition education. The study was conducted at SMK Atisa Dipamkara, Tangerang, from May to July 2025. A quasi-experimental design was employed involving 100 respondents assigned to VR and conventional training groups. Data were collected through knowledge tests, skills assessments, and Likert-scale satisfaction questionnaires. The findings demonstrate significant improvements in knowledge and skills among participants receiving VR training (p < 0.001), with outcomes superior to the conventional group. High satisfaction scores (M = 4.36; SD = 0.53) reflected strong perceptions of realism, interactivity, engagement, and active participation. VR-based training effectively addresses critical gaps in school preparedness and represents a strategic approach for strengthening comprehensive safety and health promotion programmes in educational settings.